2014
DOI: 10.1002/lary.24708
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fidelity: How expert behavior changes in a virtual reality environment

Abstract: Slight differences in drill interaction between a virtual environment and the real world can have measurable effects on surgical technique, particularly in terms of stroke length, duration, and curvature. It is important to understand these effects when designing and implementing surgical training programs based on VR simulation--and when improving the fidelity of VR simulators to facilitate use of a similar technique in both real and simulated situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Indeed, data indicate that novices and experts alike regularly fail instructions and inadvertently expose critical structures such as the facial nerve or the dura in the simulator. Visual cues are important for this, and it seems that expert performance in simulation requires higher graphic fidelity and haptic realism …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, data indicate that novices and experts alike regularly fail instructions and inadvertently expose critical structures such as the facial nerve or the dura in the simulator. Visual cues are important for this, and it seems that expert performance in simulation requires higher graphic fidelity and haptic realism …”
Section: Discussionmentioning
confidence: 99%
“…A consensus‐based approach, which has worked fine in the development of objective, structured assessment tools, can be difficult considering the complexity of simulator‐gathered performance metrics such as volume removed per minute, path length, and forces applied. Also, it can be argued that experts do not always practice what they teach, and furthermore, it has been demonstrated that expert behavior changes in a VR simulation environment compared with human cadaveric temporal bone dissection . In the expert performance framework, the superior performance of experts is used in the design of learning experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens were prepared the night before the bootcamp. Cadaveric models were selected because cadavers typically are considered the gold standard when surgical/procedural simulators are devised and tested; for instance, in a recent study by Ioannou et al, a virtual reality mastoidectomy model was compared against a cadaveric temporal bone model …”
Section: Methodsmentioning
confidence: 99%
“…Cadaveric models were selected because cadavers typically are considered the gold standard when surgical/procedural simulators are devised and tested; for instance, in a recent study by Ioannou et al, a virtual reality mastoidectomy model was compared against a cadaveric temporal bone model. 6 Artificial blood was created using low-cost materials (saline, red food coloring, and corn starch). It was delivered into the tonsillar fossa via IV tubing passed from an incision in the temporal line, which was then directed through the infratemporal fossa, medial to the mandible, through the parapharyngeal space, and through a mucosal incision in the tonsillar fossa.…”
Section: Tonsil Task Trainers For Management Of Posttonsillectomy Blementioning
confidence: 99%
“…They compared drilling techniques to those used by the same experts on real temporal bones. The authors found that drilling technique was different in the simulation and discussed the aspect of fidelity with respect to the haptic model used for the virtual simulation [36]. …”
Section: Discussionmentioning
confidence: 99%